ОСНОВНІ ТЕНДЕНЦІЇ РОЗВИТКУ ВЕНТИЛЬНО-ІНДУКТОРНИХ ДВИГУНІВ ДЛЯ КОМЕРЦІЙНИХ БПЛА - Бібік, О.В. (Інститут електродинаміки Національної академії наук України, 2025)
The article provides an overview of the design features, advantages, and disadvantages of motors used for commercial unmanned aerial vehicles. A review and analysis of multiphase classical SRMs is presented. A comparative analysis of the technical performance of an outer rotor SRM аnd PMSMs is presented, Based on a review of approaches to the design and effective methods of controlling the speed of switched reluctance  motors of electromechanical systems with variable load, the main development trends and ways of further research into SRM for commercial unmanned aerial vehicles have been identified. Ref. 10, fig. 3.